(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
يدرس هذا البحث مدى إمكانية استخدام ظاهرة تسطح الذروة كمشعر لإنتشار الامتصاص خلال الستة الأشهر الأولى من المعالجة التقويمية وذلك من خلال تقييم الامتصاص على المقطعين المحوريين المتتاليين الأول والثاني للذروة المصابة بالامتصاص؛ تألفت مواد البحث من صور طبقية محورية وثلاثية الأبعاد ل 100 مريض (76 أنثى و24 ذكراً) خضعوا لمعالجة تقويمية بتقانات مختلفة, حيث تم إجراء الصور المذكورة باستخدام جهاز طبقي محوري حلزوني و بمعدل ثلاث صور لكل مريض جميع الصور بحيث كانت الأولى(t1) قبل المعالجة والثانية(t2) بعد مضي 3 أشهر من المعالجة و الثالثة (t3) بعد مضي 6 أشهر؛ تمت مقارنة كل متغير شعاعي أصيبت به جذور الأسنان في المرحلة (t1) مع ما يقابلها في كلٍ من المرحلتين (t2) و وذلك باستخدام اختبار t الإحصائي عند مستوى الدلالة: P< 0.05؛ أكدت هذه الدراسة إمكانية استخدام ظاهرة تسطح الذروة كمشعر لانتشار الامتصاص خلال الستة الأشهر الأولى من المعالجة التقويمية وذلك من خلال تقييم الامتصاص على المقطع المحوري الأول ولكن ليس على المقطع المحوري الثاني، كما بينت هذه الدراسة أن عملية امتصاص الجذور تنطلق مبكراً خلال الأشهر الثلاثة الأولى من بداية المعالجة التقويمية. The aim of this study is to evaluate the possibility of using the phenomenon of extend of the resorption on sectional area on the first two successive c.t. axial sections of the apex of the teeth root as radiographic parameter of the root resorption during the orthodontic treatment; Axial CT-scans and C.T. reconstructed 3-D graphs of 76 females & 24 males were taken; patients were treated with different kinds of orthodontic techniques. All graphs were taken by a Spiral C.T. at the beginning (T1), after 3 (T2) and 6 months (T3) of the treatment; tooth length and extend of the resorption on sectional area on first and second axial slices were studied. Every variable in each stage was compared with the same variable in other stages using T-test(P< 0.05). The current results reveal that the extend of the resorption on sectional area on the first axial slice on the successive C.T. axial sections of the apex of the teeth root can be used as an early radiographic index of root resorption at the beginning of orthodontic treatment, but not the second axial slice; in addition, most changes took place during the first 3 months of orthodontic treatment.